Comparative evaluation of metal ions release from titanium and Ti-6Al-7Nb into bio-fluids - Lori A Joseph; Omoniyi K Israel; Ekanem J Edet (Wolters Kluwer Medknow Publications, 2009)
Background: The study was designed to investigate the effects of pH, chloride ions and nature of some bio-fluids on the amount of metal ions released from titanium and TiAl 6 Nb 7 plates following incubation in actual and simulated bio-fluids over time. Methods: The amounts of released metal ions from commercially pure titanium (CpTi) and TiAl 6 Nb 7 of surgical grade on immersion in 20 mL Hank's solution of pH 4.0 or 7.0, Hank's solution of high chloride ions concentration, Whole Blood Serum (WBS) and Phosphate Buffered Saline (PBS) at 37° C were determined over an incubation time of 20 weeks using atomic absorption spectrophotometry. The levels of released metal ions were compared by two-way ANOVA and Duncan's post-hoc tests. The amounts of titanium ions released by the samples were analyzed by Pearson's correlation. Results: TiAl 6 Nb 7 plate showed no release of Ti ions into the test solutions until after 12 weeks of incubation, while Ti ions were released from the CpTi plate from the 1 day immersion time. The re-lease of measurable amount of Al ions from TiAl 6 Nb 7 was after 12 weeks of incubation. The rate of release of Ti and Al ions from the samples increased initially with incubation time and then stabilized due to adsorption-desorption equilibrium. Conclusion: The results showed that variations in pH and chloride ions of the test media has a sig-nificant effect on the amounts of Ti ions released, while increase in chloride ions concentration sig-nificantly elevates the release of Al ions into the bio-fluids.